“It’s a reasonable gamble”—rural residents’ experience participating in cancer clinical trials at a single rural trial unit - McPhee, Narelle J.; Hughes, Diane; Ristevski, Eli (Current controlled trials in cardiovascular medicine, 2025)
Background We conducted a qualitative study to examine what factors influence rural-residing people with cancer to participate in cancer clinical trials (CCT) and what factors influence their retention in CCT. Methods Purposive sampling was used to recruit participants from a regional cancer centre in Victoria, Australia, to participate in a semi-structured interview. Eligible participants were ≥ 18 years of age at the time of cancer diagnosis, newly consented to a clinical trial (< 1 year) or have been a trial participant for ≥ 1 year, lived in a non-metropolitan area classified within the Monash Modified (MM) Model 2–7 and able to provide informed consent. Thematic analysis was used to analyse the interview data. Results Seventeen participants were interviewed; 10 identified as female and seven as male. Participant’s ages ranged from 52 to 77 years, with a median age of 62 years. Eight participants had been on a CCT for ≤ 1 and 10 for ≥ 1 year. Factors that influenced their decision to participate in a CCT included trust and confidence in clinical trial staff, exposure to and trust in the experiences of cancer peers, altruism, low-risk trials and local access to trials. The factors influencing their decision to remain in a CCT included balancing the benefits and burdens of the trial, having no doubts about participating despite knowing the risks and seeing the personal benefits of participating in a CCT. Conclusion Our study shows that trust-based relationships, peer support, and altruism encourage rural residents to participate in CCT. To improve access to CCT for rural residents, a multi-faceted approach involving clinicians, health services, trial sponsors and policymakers is needed. These approaches must promote and facilitate the inclusion of diverse populations, prioritise CCT participation, and inform patients of CCT opportunities. We must recognise the knowledge and expertise of rural patients and caregivers and ensure they are involved as co-designers of future CCTs.